DEVELOPING DIFFERENTIATED ELECTRONIC SUPPLEMENTARY READING EXERCISE FOR THE SLOW LEARNERS OF SEVENTH YEAR STUDENTS AT SMP N 2 SINGARAJA - Dewi, N.N.A.U. (International Journal of Language and Literature, 2017)
Integrating ICT in learning has become the demands of Curriculum 2013. Yet, not all of the teacher have media to support the integration of ICT in learning. Whereas, the integration of ICT may help the teachers to accomodate students’ diversity by using differentiated instruction. Thus, this study aimed at: (1) identifying kinds of supplementary reading exercises are needed by the Seventh Year Students at SMP N 2 Singaraja; (2) identifying the design of the electronic supplementary reading exercises for the slow learners of seventhyear students at SMP N 2 Singaraja; (3) measuring the quality of the electronic supplementary reading exercises for the slow learners of seventhyear students at SMP N 2 Singaraja. This study was conducted based on the research and development design proposed by Sugiono (2011). The data of the study were collected through questionnaire, interview, observation, expert judge and field study. The results of the data were further analyzed by using descriptive analysis and interrater agreement model from by Gregory (2000). The result of the study showed that (1) the supplementary reading exercise needed by the seventh year students at SMP N 2 Singaraja was supplementary reading exercise which was integrated with ICT; (2) the design of the electronic supplementary reading exercise for the slow learners was developed based on the needs; (3) the electronic supplementary reading exercise for the slow learners was categorized as high quality exercises based on content validity, empirical validity, quality of the media and field test.